PENANGANAN PASCAPANEN KOPI ROBUSTA BASEH TERHADAP ORGANISME PENGGANGGU TANAMAN : TINJAUAN - Novianti, Rika; Rahayuniati, Ruth Feti; Suroto, Agus (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Baseh Village, Kedungbanteng Subdistrict, Banyumas Regency, located on the slopes of Mount Slamet in Central Java, specializes in the production of coffee. With an elevation of approximately 700 meters above sea level, the majority of Baseh Village's residents cultivate robusta coffee. Robusta coffee (Coffea canephora) is known for its stronger and more bitter flavor, as well as its higher caffeine content. These coffee beans are processed and used to make coffee beverages. To ensure the production of high-quality coffee, proper post-harvest handling is essential. One of the challenges is dealing with plant pests (Pest organisms). Post-harvest pests that affect coffee beans include the coffee berry borer (CBB), scientifically known as Hypothenemus hampei, and microfungi like Fusarium sp., which causes bean rot. This overview provides insights into post-harvest coffee pests and their management efforts, which are expected to be beneficial for the Baseh Village community. Keywords: Coffee, CBB, Hypothenemus hampei, microfungi.